PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN SBDP MATERI MEMBUAT SOUVENIR DENGAN TEKNIK ANYAMAN SISWA KELAS V SDN 013 MARANGKAYU - Muhammad Ari Sulianto; Muhlis; Usfandi; M.Ramli; Sukriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the decline in learning outcomes of 5th-grade students at SD Negeri 013 Marangkayu in SBdP learning. Based on the problem formulation above, the objective of this research is